When my teachers think I can, then I know I can: A systematic review - Rubie-Davies, Christine; Li, Mengnan (Studies in Second Language Learning and Teaching, 2025)
This systematic review investigated teacher expectations of students learning an additional language, in the context of either immigrant students as a minority in the classroom or of all majority-group students learning a foreign language together. Only 28 studies could be located. The review found some negative teacher expectations and beliefs towards and about immigrant students. Most teachers appeared to lack training for teaching their second language learners (SLLs), but many appeared reluctant to engage in additional professional development because the offerings were considered inadequate. However, some studies offered detailed descriptions of teacher practices that had significantly increased their SLLs’ learning and psychosocial outcomes. Given the multicultural nature of many of today’s classrooms, there is a clear need for additional studies in this field and for high-quality professional development.